Fortified Withaferin A accelerates the transition from fibrovascular to bone remodeling phase during endochondral bone formation to promote ossification - Chutani, Kunal; Rai, Nikhil; Sardar, Anirban; Yadav, Anupama; Rai, Divya; Raj, Anuj; Maji, Bhaskar; Verma, Shikha; Tripathi, Ashish Kumar; Dhaniya, Geeta; Hingorani, Lal; Mishra, Prabhat Ranjan; et al. (Frontiers in Endocrinology, 2025)
IntroductionThis study shows that Fortified Withaferin A (FWA, 10% w/w) accelerates bone healing, advancing from the fibrovascular to bone remodeling stage within 12 days, compared to the typical 23–24-day healing time in rodents. FWA (10% w/w) outperformed parathyroid hormone (PTH) in osteoclast regulation and minimized recovery time, highlighting its potential as a therapeutic agent for bone health.MethodsFWA (10% w/w) was administered orally at 125 mg·kg–1. A transverse osteotomy model was used to assess post-natal bone regeneration. Additionally, an estrogen-deficient model was employed to evaluate the therapeutic potential of FWA (10% w/w). Bone regeneration was validated through calcein incorporation, gene expression analyses, micro-CT imaging and mechanical testing. Pharmacokinetic profiling was used to determine plasma exposure and trough concentration.ResultsFWA (10% w/w) effectively downregulated bone-resorbing genes, promoted anabolic responses, and reduced inflammation. It enhanced post-natal bone regeneration, likely via Runx-2 activation and modulation of osteogenic genes, alongside suppression of E3 ubiquitin-ligases Smurf1 and Smurf2, resulting in significantly enhanced callus formation and healing speed. Micro-CT revealed an enhanced callus area of ~95.14% within 12 days, compared to ~72.87% associated with normal healing. In the estrogen-deficient model, FWA (10% w/w) led to ~83.88% bone volume fraction at 23 days, exceeding the ~76.80% in controls and matching PTH effects. Material stiffness showed significant gains, with average Young’s modulus rising from ~54 ± 1.03 MPa to ~63 ± 2.54 MPa. Pharmacokinetic profiling indicated plasma exposure at 226 ng/ml*hr and higher trough concentration at 24 hr, contributing to optimum therapeutic effectiveness.DiscussionThese results demonstrate that FWA (10% w/w) could significantly enhance bone mineralization and healing, facilitating an earlier transition from fibrovascular tissue to bone remodeling. The enhanced results, such as increased healing, better callus formation, and improved mechanical properties, indicate that FWA (10% w/w) is a potential intervention for delayed healing, especially in osteoporotic fractures.